2017
DOI: 10.1021/acs.jpcb.7b00103
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Bionanocomposites from Epoxidized Hemp Seed Oil Thermosetting Resin Reinforced with Halloysite Nanotubes

Abstract: Hemp seed (Cannabis sativa L.) oil comprises a variety of beneficial unsaturated triglycerides with well-documented nutritional and health benefits. However, it can become rancid over a relatively short time period, leading to increased industrial costs and waste of a valuable product. The development of sustainable polymers is presented as a strategy, where both the presence of unsaturation and peroxide content could be effectively used to alleviate both the waste and financial burden. After the reaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Moreover, HO can be easily obtained by cold-pressing the seeds or using organic solvents [ 33 ] and is characterized by a high content of linoleic (n-6) and α-linolenic (n-3) fatty acids [ 34 ]. Due to its high unsaturation content, the HO allows a wide variety of chemical modifications, such as epoxidation, acrylation, hydroxylation or maleinization [ 35 , 36 ]. These modifications increase the vegetable oil’s reactivity by improving its interaction with the polymeric matrix, giving it a greater plasticizing effect than unmodified vegetable oil.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HO can be easily obtained by cold-pressing the seeds or using organic solvents [ 33 ] and is characterized by a high content of linoleic (n-6) and α-linolenic (n-3) fatty acids [ 34 ]. Due to its high unsaturation content, the HO allows a wide variety of chemical modifications, such as epoxidation, acrylation, hydroxylation or maleinization [ 35 , 36 ]. These modifications increase the vegetable oil’s reactivity by improving its interaction with the polymeric matrix, giving it a greater plasticizing effect than unmodified vegetable oil.…”
Section: Introductionmentioning
confidence: 99%
“…that makes it interesting for polymer synthesis, modification, and composite manufacturing [38][39][40][41][42]. Shuttleworth et al [43] have recently reported the fabrication of flexible bio-based nanocomposites from epoxidized hemp seed oil (EHO) as thermosetting resin with halloysite nanotubes (HNTs). Manthey et al [40] reported interesting green composites based on EHO thermosetting matrix and hemp fiber reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…To improve epoxy resins' comprehensive properties (mechanical properties, rheological properties, electrical, and thermal conductivity, etc.) and reduce costs, fillers are often required, such as, silica particles, [6][7][8] carbon nanotubes, [9][10][11][12] rubber particles. 13 In this context, because of the high Si O bond energy, which causes the particularly high-thermal stability of nano-SiO 2 , nano-SiO 2 particles are widely used to enhance the heat-resistant properties and mechanical properties of epoxy resins.…”
Section: Introductionmentioning
confidence: 99%